Mind Mapping to Teach Writing in Descriptive Text - Sherly Citra Putri; Ratna Sujiati (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This research article discussed the effectiveness of mind mapping to teach writing descriptive text. In this case, the subject of research was 32 students of English Department, Faculty of Teacher Training and Education in Mayjen Sungkono University of Mojokerto. This article was aimed to use qualitative pre-experimental research design. The finding showed a significant different score between the pre-test and post-test. It indicated that mind mapping was effective to teach writing descriptive text.